Molecular Detection of SV40, BKV and JCV in Esophageal and Colorectal cancer Patients in Khartoum State, Sudan (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: BKV; JCV; and SV40; colorectal cancer; esophageal cancer; khartoum state; Sudan